Social, Nature, Religion Morality and Protecting Of Pencak Silat Cimande - Bahagia Bahagia; Rimun wibowo; Dede Dede; Fitri Amelia; Kartika Amelia; Ilham Nur Hidayat; Mulyana Kosasih (Universitas Pahlawan Tuanku Tambusai, 2021)
Pencak silat is part of the Indonesian culture that plays a role in shaping morals towards the environment. This study aims to find the moral values and conservation of the Cimande pencak silat. The research method used is a qualitative method. Collecting data by observation, in-depth interviews, and documentation. Selection of informants with purposive sampling technique. Data analysis with data triangulation approach. The findings show that Cimande pencak silat has moral values to God, humans and the environment. If the opponent has lost, they must be respected by not hitting the opponent and insulting the opponent and not being allowed to step on the opponent. Likewise, with nature, Cimande members are not allowed to throw garbage into the river and treat living creatures like animals properly. Another finding there are several way to protect pencak silat from extinction such as releasing literacy to youth about silat, modifying the method and categorizing silat players from junior and senior as well as promote silat at school. Another finding is that there are health values from the Cimande silat game and contains religious values and there are social values from Cimande pencak silat activities